Can Entrepreneurship Enable Economic and Social Integration of Refugees? A Comparison of the Economic, Social and Policy Context for Refugee Entrepreneurship in the UK and Germany*. Issue 1 (January 2023) - Schmich, Marilena; Mitra, Jay
This article examines critically the support systems necessary for economic integration of refugees by analysing the economic, social and policy context of refugee entrepreneurship in Germany and the UK. Current economic integration policies in both countries focus primarily on assisting refugees to find employment while appearing to neglect the value of refugee entrepreneurship as a viable option for integrating refugees into the destination country's economy. Assuming economic integration of refugees is a fundamental socio-economic goal in both countries, our aim was to examine the challenges that could be addressed with regard to future policies for targeting refugee entrepreneurship and augmenting both entrepreneurship development and entrepreneurial policy formulation in host societies. We introduce a theoretical framework building onWauters and Lambrecht (2008, Journal of Ethnic and Migration Studies, 34 (6), 895–915) and use inductive thematic analysis (Guest et al., 2013, Collecting qualitative data: A field manual for applied research ) to examine which variables impact refugees. We identify how regulations, measures and policies in different environments affect those variables. We also examine the concept of mixed embeddedness (Kloosterman et al., 1999, International Journal of Urban and Regional Research, 23 (2), 252–266), and its appropriateness for understanding the emergent entrepreneurial activity of refugees and the support systems that can aid opportunity-based integration. Our findings show that first, the most common challenges refugee entrepreneurs encounter are (a) seed capital, (b) language barriers, (c) location, (d) embeddedness and (e) knowledge about the local market. Second, there are no significant differences in the challenges that refugee entrepreneurs encounter, between the UK and Germany. Third, we also find that the support system for refugee entrepreneurs is larger in Germany than in the UK due to the capacity of government and civil society support. We conclude that combating downward occupational mobility, and fully using the potential and expertise of refugees, refugee entrepreneurship could be considered as a viable option for economic integration because refugee communities offer unique opportunities for potentially expanding the scope and style of entrepreneurship in host countries.